A novel physical device to realize rate-independent linear damping for performance enhancement of seismically isolated structures. (1st March 2023) - Luo, H.; Tang, Z.A.; Zhu, H.P.
Abstract: It is common concerned that seismically isolated structures may suffer excessive responses when subjected to extreme ground motions containing dominated long-period components. Supplementing damping via traditional damping devices is indeed beneficial in reducing the isolator displacement but perhaps at the expense of floor response accelerations. In the previous study, a conceptual rate-independent linear damping model (known as MNS model), which consists of linear Maxwell and negative stiffness elements in parallel, was found to be capable of simultaneously controlling response displacements and floor accelerations of low-frequency structures under strong ground motions. In the present study, a novel damping device, referred to as Maxwell-negative-stiffness damper (MNSD), is proposed to physically realize the conceptual rate-independent MNS model, and an efficient method of designing the properties of the MNSD with its nonlinearity embedded is presented. The performance of the proposed MNSD incorporated into a seismically isolated building structure is systematically studied by using both short- and long-period ground motions, and parametric studies are conducted to investigate the influences of key characteristic parameters on the control capability of the MNSD. Numerical examples illustrate the advantages of the proposed MNSD over the commonly used fluid viscous and hysteretic dampers, as well as the conventional negative stiffness dampers, in improving the performance of seismically isolated building structures under both sets of short- and long-period ground motions. Highlights: Proposing a novel damping device to realize the rate-independent linear damping. Developing an efficient method of designing the nonlinear device properties. Achieving simultaneous reduction on isolator displacements and floor accelerations. Examining devices' capacity by parametric studies under short and long-period waves. Identifying the device's considerable advantages over commonly used damping devices.